Digital Transformation of Small Businesses In Medan: A Quantitative Exploration of The Mediating Role of Partnerships in Enhancing E-Commerce Effectiveness - Sitorus, Sunday Ade; Simanjuntak, Sri Ida Royani; Sipayung, Leonardo David; Simarmata, Candra A.; SUNDAY ADE SITORUS (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to explore the effect of digital transformation on increasing e-commerce effectiveness through the mediating role of partnerships in small businesses in Medan City. This research focuses on digitalization strategies that can strengthen the competitiveness of small businesses in the digital economy era. The originality of the research lies in the quantitative approach that examines the relationship between digital transformation, partnership, and e-commerce effectiveness, which has not been widely studied in the context of small businesses in Medan. The research gap identified is the lack of understanding on how partnership can mediate the impact of digital transformation on e-commerce effectiveness. The method used was a quantitative survey with SEM-PLS technique to analyze data collected from 200 small business owners in 21 sub-districts in Medan. The research findings show that digital transformation has a significant influence on partnerships, but does not directly have a significant effect on e-commerce effectiveness. In addition, partnership does not have a significant mediating role between digital transformation and e-commerce effectiveness. The conclusion of this study is that small businesses in Medan need a more integrated digital strategy and adequate infrastructure support to improve e-commerce effectiveness through stronger partnerships.